Special section “Case Reports in Otolaryngology” - Bradley, Patrick J. (AME Case Reports; Vol 2 (January 2018): AME Case Reports, 2018)
I have been invited to join the Editorial Board of AME Case Reports (ACR) and head up the Section “Case Reports in Otolaryngology”. While case reports tend to be misunderstood—more so by journal editors and academics because of their poor quality and “lowering the impact factor” of the journal in which it appears! Most academics were one time trainees and if they be honest their career in publishing must have included a number of “case reports”? (1).